2020
DOI: 10.1186/s12936-020-03377-4
|View full text |Cite
|
Sign up to set email alerts
|

Human plasma plasminogen internalization route in Plasmodium falciparum-infected erythrocytes

Abstract: Background: The intra-erythrocytic development of the malaria parasite Plasmodium falciparum depends on the uptake of a number of essential nutrients from the host cell and blood plasma. It is widely recognized that the parasite imports low molecular weight solutes from the plasma and the consumption of these nutrients by P. falciparum has been extensively analysed. However, although it was already shown that the parasite also imports functional proteins from the vertebrate host, the internalization route thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Upon P. falciparum infection of RBCs, we have demonstrated that BCL-x L continues to localize to the host RBC cytosol but that a pool of the protein relocates either to the parasitophorous vacuole membrane, the parasite membrane, or within the parasite itself (Figure 3). P. falciparum is known to export a considerable number of proteins to its host cell, including many targeted to the RBC membrane, but only a few examples of functional human proteins have been shown to be imported by the parasite [45][46][47][48]. Further work is required to identify the exact subcellular localization of BCL-x L in iRBCs, and similar investigations should be carried out in infected hepatocytes.…”
Section: Bcl-x L Is Recruited To the Parasite Upon Infectionmentioning
confidence: 99%
“…Upon P. falciparum infection of RBCs, we have demonstrated that BCL-x L continues to localize to the host RBC cytosol but that a pool of the protein relocates either to the parasitophorous vacuole membrane, the parasite membrane, or within the parasite itself (Figure 3). P. falciparum is known to export a considerable number of proteins to its host cell, including many targeted to the RBC membrane, but only a few examples of functional human proteins have been shown to be imported by the parasite [45][46][47][48]. Further work is required to identify the exact subcellular localization of BCL-x L in iRBCs, and similar investigations should be carried out in infected hepatocytes.…”
Section: Bcl-x L Is Recruited To the Parasite Upon Infectionmentioning
confidence: 99%
“…Mechanisms of sporozoite and merozoite invasion into hepatocytes and erythrocytes, respectively, and development within the host cell have been the subject of extensive research. In the blood stage, the mechanisms of nutrient uptake across the host red cell membrane, parasitophorous vacuole membrane (PVM) and parasite plasma membrane (PPM) have received much focus due to the trafficking of multiple parasite proteins to the host cell membrane through the Maurer’s clefts, tubovesicular membranes and other mobile membranous vesicles like the J-dots [ 2 , 3 ]. The transport of nutrients from the extracellular environment into the host erythrocyte and from the host cell cytoplasm into the parasite, although significant, have received less attention, in part, due to the challenges of investigating the trafficking pathways.…”
mentioning
confidence: 99%